Penerapan Efektivitas E-Government Kecamatan Kaliorang Kabupaten Kutai Timur - Siti Hadijah (Universitas 17 Agustus 1945 Samarinda, 2020)
e-Government is a system Subdistrict application which caused for transaction processing and monitoring the creation of documents that exist in the government district of e-Government Sub-district is one of the application services of the program Smart City declared by regent and Vice Regent of East Kutai Regency is an effort of the government in developing a system of effective governance, efficient and transparent by optimizing the use of Information Technology systems. e-Government Sub-district is now implemented by 6 Kaliorang village in the district of East Kutai Regency, one of which the District Kaliorang. Then the unit of analysis in the present study the implementation of E-Government Kaliorang District of East Kutai. This type of research used by the authors in this research is descriptive qualitative. Data collection technique were interview, observation and documents related to the study. Data analysis techniques in the study conducted qualitatively. The results of this study explained that the implementation of e-Government Kaliorang District of East Kutai Regency was quite effective. It is measured based on indicators measuring the effectiveness by Gibson.e-Government merupakan sistem aplikasi Kecamatan yang menyebabkan untuk pemrosesan transaksi dan pemantauan pembuatan dokumen yang ada di lingkungan pemerintah kecamatan e-Government merupakan salah satu layanan aplikasi program Smart City yang dinyatakan oleh Bupati dan Wakil Bupati Kabupaten Kutai Timur merupakan upaya pemerintah dalam mengembangkan sistem tata kelola pemerintahan yang efektif, efisien dan transparan dengan mengoptimalkan penggunaan sistem Teknologi Informasi. Kecamatan e-Government kini dilaksanakan oleh 6 desa Kaliorang di kecamatan Kabupaten Kutai Timur, salah satunya Kecamatan Kaliorang. Kemudian unit analisis dalam kajian saat ini pelaksanaan E-Government Kecamatan Kaliorang Kutai Timur. Jenis penelitian yang digunakan oleh penulis dalam penelitian ini bersifat deskriptif kualitatif. Teknik pengumpulan data adalah wawancara, observasi dan dokumen yang terkait dengan penelitian ini. Teknik analisis data dalam penelitian ini dilakukan secara kualitatif. Hasil penelitian ini menjelaskan bahwa pelaksanaan e-Government Kaliorang Kecamatan Kutai Timur cukup efektif. Hal ini diukur berdasarkan indikator yang mengukur efektivitas oleh Gibson.